circTADA2A Retards the Progression of Colorectal Cancer via Regulating miR-1229/BCL2L10 Signal Axis - Hu L; Fang L; Zhang Z; Yan Z (Cancer Management and Research, 2021)
Li Hu, Lei Fang, Zhiping Zhang, Zhilong Yan Department of Gastroenterology, Ningbo No.1 Hospital, Ningbo, People’s Republic of ChinaCorrespondence: Zhilong YanDepartment of Gastroenterology, Ningbo No.1 Hospital, 59 Liuting Street, Haishu District, Ningbo, 315000, Zhejiang Province, People’s Republic of ChinaEmail yanzhilong@nbu.edu.cnBackground: Colorectal cancer (CRC) is one of the leading causes of cancer-related death around the world, becoming a severe public health problem. Mounting evidence has proven that circRNAs act as pivotal modulators in the initiation and development of CRC. Although the function of circTADA2A has been explored in osteosarcoma and breast cancer, the specific role of circTADA2A in CRC remains unknown.Methods: Bioinformatics analysis based on GEO datasets was used to evaluate the dysregulated circRNAs in CRC. CCK-8 and transwell assays were used to detect the functions of CRC cells. qRT-PCR and Western blot were performed to evaluate the expression of RNAs and proteins. Luciferase assay and RNA pull down experiment were carried out to verify the interaction between miR and its targets.Results: CircTADA2A was downregulated in CRC tissues compared with normal samples. CircTADA2A exhibited greater stability than its linear form when exposed to RNase R and actinomycin D treatment. qRT-PCR analysis validated the lower expression level of circTADA2A in CRC. The loss-of-function and gain-of-function assays indicated that circTADA2A exerted the inhibitory role in CRC cell proliferation and migration. Mechanistically, circTADA2A functioned as a sponge of miR-1229. Further experiments manifested that circTADA2A regulated BCL2L10 expression via competitively binding to miR-1229. More importantly, the tumor suppressor role of circTADA2A in the malignant behaviors of CRC cells was mediated by BCL2L10.Conclusion: circTADA2A suppressed cell proliferation and migration in CRC through regulation of miR-1229/BCL2L10 axis, which suggested that circTADA2A might represent a novel potential target for the treatment of CRC.Keywords: colorectal cancer, circTADA2A, miR-1229, BCL2L10